3-D water properties and geostrophic circulation on the eastern Bering Sea shelf. (December 2016) - Cokelet, Edward D.
Abstract: The National Oceanic and Atmospheric Administration׳s (NOAA) Alaska Fisheries Science Center bottom trawl survey samples demersal fish at over 350 sites on the eastern Bering Sea continental shelf each summer on a 37×37 km 2 grid. Rugged conductivity–temperature-depth sensors (CTDs) were added to the net hauls to obtain gridded data sets of temperature and salinity measurements for 2008–2010. Results reveal the three-dimensional thermohaline structure of the shelf including the Cold Pool and areas of fresher water around St. Matthew Island and in Bristol Bay. Horizontal gradients are often strongest roughly along the 50-m and 100-m isobaths that traditionally separate the inner- and outer-shelf from the middle-shelf centered along the 70-m isobath. The summer mixed layer depth is less than 30 m over much of the region. It reaches the bottom along the Alaska Peninsula in water depths greater than 70 m, showing that the boundary of the well-mixed, inner shelf is not always at the 50-m isobath. The greatest upper-to-lower layer density difference is found across the shelf north of 59°N. The salinity difference is the main contributor to this density difference over most of the region in 2008 and 2010, but the temperature difference dominates in 2009 due to decreased ice melt and reduced freshening near St. Matthew Island. The geostrophic velocity relative to the bottom shows northwestward flow seaward of the 100-m isobath and northwestward transports integrated across the shelf of 0.10–0.25×10 6  m 3 /s. In 2008 and 2010 there was clockwise circulation in a region of less-saline water around St. Matthew Island. In 2009 that fresher lens did not exist, and flow was more concentrated along the 100-m isobath bringing saltier water across the shelf.